ANALISIS KELAYAKAN USAHA MINYAK SERAI WANGI PADA KONDISI RISIKO (STUDI KASUS PT. MUSIM PANEN HARMONIS) - Windias Farah Nabila; Rita Nurmalina (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2019)
Citronella oil is one of the essential oils commodity that has great potential to become a business. PT. Musim Panen Harmonis is a company that produce citronella oil. Cultivation and distillation business of Citronella needs a lot of investment costs and cant be separated from the possibility of production and price risk that will affect the feasibility of the business. The purpose of this study is to determine the feasibility of citronella oil refining non-financial and financial conditions both normal and risk conditions. The research methods used feasibility analysis of non-financial aspects, financial aspect, and scenario analysis with risk assessment. PT. Musim Panen Harmonis is worth to do of non-financial and financial aspects. In normal condition, NPV value is Rp. 7.415.711 072, IRR value is 14.02 persen, Net B/C value is 1.65, and Payback period is nine years one month long. While financial analysis though the risk condition also gain value that full fill investment standart criteria. Then based on the risk assessment said that production risk has higher level than price risk. It means when the business of PT Musim Panen Harmonis face off the production risk it will gain more loss. Advice given to this effort is to optimize production through increased number of citronella plant populations and the use of all land in accordance with the goals and plans, and the company needs to make a contract with partners on the lowest price limit.